OССUPATIONAL AND CHRONIC NON-COMMUNICABLE DISEASES IN GLASS FIBER MANUFACTURING WORKERS - G. F. MUKHAMMADIYEVA; Z. F. GIMAEVA; A. B. BAKIROV; L. K. KARIMOVА; E. T. VALEYEVА; D. O. KARIMOV (Кубанский научный медицинский вестник, 2017)
The aim of the study was to determine the prevalence of chronic non- communicable diseases among glass fiber manufacturing workers to develop effective measures for the prevention. A total of 71 patients with occupational skin tumors were examined. Retrospective analysis of the medical records of these patients was performed. The results of the study showed that hyperkeratosis and skin cancer prevailed in the structure of occupational diseases. Priority concomitant chronic non-infectious disorders in workers with occupational skin tumors are diseases of the circulatory system. Multidirectional changes in a number of hematological parameters were found depending on the nosological form of occupational skin neoplasms. The results are the basis for the development of complex organizational and hygienic and medical preventive measures, aimed at maintaining the health of glass fiber manufacturing workers.